EULAR report on the use of ultrasonography in painful knee osteoarthritis. Part 1: Prevalence of inflammation in osteoarthritis. Issue 12 (5th May 2005) - D'Agostino, M A; Conaghan, P; Le Bars, M; Baron, G; Grassi, W; Martin-Mola, E; Wakefield, R; Brasseur, J-L; So, A; Backhaus, M; Malaise, M; Burmester, G; et al.
Abstract : Objectives: To assess the prevalence of inflammation in subjects with chronic painful knee osteoarthritis (OA), as determined by the presence of synovitis or joint effusion at ultrasonography (US); and to evaluate the correlation between synovitis, effusion, and clinical parameters. Methods: A cross sectional, multicentre, European study was conducted under the umbrella of EULAR-ESCISIT. Subjects had primary chronic knee OA (ACR criteria) with pain during physical activity ⩾30 mm for at least 48 hours. Clinical parameters were collected by a rheumatologist and an US examination of the painful knee was performed by a radiologist or rheumatologist within 72 hours of the clinical examination. Ultrasonographic synovitis was defined as synovial thickness ⩾4 mm and diffuse or nodular appearance, and a joint effusion was defined as effusion depth ⩾4 mm. Results: 600 patients with painful knee OA were analysed. At US 16 (2.7%) had synovitis alone, 85 (14.2%) had both synovitis and effusion, 177 (29.5%) had joint effusion alone, and 322 (53.7%) had no inflammation according to the definitions employed. Multivariate analysis showed that inflammation seen by US correlated statistically with advanced radiographic disease (Kellgren-Lawrence grade ⩾3; odds ratio (OR) = 2.20 and 1.91 for synovitis and joint effusion, respectively), and with clinical signs and symptoms suggestive of an inflammatory "flare", such as joint effusion on clinical examination (OR = 1.97 and 2.70 for synovitis and joint effusion, respectively) or sudden aggravation of knee pain (OR = 1.77 for joint effusion). Conclusion: US can detect synovial inflammation and effusion in painful knee OA, which correlate significantly with knee synovitis, effusion, and clinical parameters suggestive of an inflammatory "flare".